La fotografía como elemento de identidad cultural en el ser humano, una mirada desde el arte. - Terán Yépez, Byron Javier (2018)
From the origin of Humanity the human being has created assumptions that allow him to create his own identity, through many means from his biological, cultural and territorial origins that allow him to identify himself. Nowadays the ignorance of the historical background provoked by cultural impositions in Latin America, times of war, political crises, migrations, globalization have created a misunderstanding in the identity. As a crucial element of identification has been the use of the portrait throughout history the way that has allowed to create a referent about us in graphic form; With the emergence of the camera this activity was popularized by the facilities that this medium provides for its execution, by giving us a highest representation to from any visual artist. Photography, becoming a transcendental element in the life of human being by its value of registration allows us through the art to create proposals that make us reflect on the critical events in life as our identity is. Artist, critics, philosophers have addressed this issue through the mechanical use of this element to reveal the existing concerns about our identity, who we are, what we project and who we believe we are.